Comparison of foci of active inflammation and fatty degeneration according to MRI and CT data of syndesmophytes in patients with ankylosing spondylitis - Magomed K. Kurbanmagomedov; Ksenia V. Sakharova; Ekaterina M. Agafonova; Margarita M. Urumova; Svetlana O. Krasnenko; Anastasia E. Dimitreva; Tatiana V. Dubinina; Shandor F. Erdes (Научно-практическая ревматология, 2024)
Introduction. Syndesmophyte, which is the hallmark of ankylosing spondylitis (AS), is a vertically oriented ossification located outside the fibrous ring of the intervertebral disc. In recent decades, the most widespread theory is that after inflammation in the area of attachment of the fibrous ring to the vertebral body, fatty degeneration occurs with reparative processes, as a result of which the growth of new bone – syndesmophyte – begins. It is believed that the likelihood of developing syndesmophyte is two to three times higher in the angles of those vertebrae in which active inflammation or fatty changes were detected on magnetic resonance tomography (MRI) in the previous 2 years, the latter having a stronger association with subsequent pathological bone formation. However, this relationship is ambiguous according to different studies.The aim – comparison of the exact localization of magnetic resonance tomography and computed tomography (CT) signs of lesions on the vertebral endplates, characteristic of axial spondyloarthritis, in patients with ankylosing spondylitis.Material and methods. The cross-sectional study included 10 patients with AS who met the inclusion criteria.All patients underwent a standard examination for AS, as well as MRI and CT examination of the lumbar spine.A special technique for joint assessment of changes detected during MRI and CT examination has been developed.For the primary analysis, changes found on the upper endplates of 5 lumbar vertebrae were taken.Results. On the upper endplates of 5 lumbar vertebrae, a CT examination revealed 35 syndesmophytes (from 1 to 7 syndesmophytes in 1 patient), and MRI revealed 9 foci of acute inflammation and 24 of chronic inflammation (fatty degeneration). When jointly analyzing the MRI foci of detectable inflammation and syndesmophytes transferred to the vertebral diagram, it turned out that in the majority of cases (68%), the latter were not associated with sites of active and/or chronic inflammation. Correlation analysis showed a certain direct relationship only between the number of syndesmophytes and foci of chronic inflammation (r=0.68).Discussion. Preliminary data show that the proposed method for comparing MRI and CT lesions in AS allows us to jointly study the localization of MRI and CT spinal injuries in patients with AS using multidirectional sections. The first results of our one-time study showed that in most cases the localization of developing syndesmophytes does not coincide with the foci of inflammation detected by MRI (both acute and chronic).